If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) + 2 = 7 Reorder the terms: 3(5 + 2x) + 2 = 7 (5 * 3 + 2x * 3) + 2 = 7 (15 + 6x) + 2 = 7 Reorder the terms: 15 + 2 + 6x = 7 Combine like terms: 15 + 2 = 17 17 + 6x = 7 Solving 17 + 6x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 6x = 7 + -17 Combine like terms: 17 + -17 = 0 0 + 6x = 7 + -17 6x = 7 + -17 Combine like terms: 7 + -17 = -10 6x = -10 Divide each side by '6'. x = -1.666666667 Simplifying x = -1.666666667
| 4r-15=-6+r | | 12+2e^2x=19 | | 4x(x^2-1)=0 | | 2(2)-x-3=0 | | 21x+3=14 | | 6s-23=-39+2s | | 10+2e^8x=30 | | 7x+4y=575 | | (4x-3)(2x+5)= | | 7x+3=23 | | 6(x-1)+3x+2= | | w(w+2)=w(10-w) | | 0.25x+1.23=2.21 | | -(7v-9)-15= | | -116-8x=218-44x | | 6x+3+5x-x+5= | | 97-3x=5x+9 | | 4x-x-7x= | | 4w+w+8=A | | (2x+4)(x+3)= | | 27-5x=4x+17 | | 26+N*17=-42 | | 21-4(9+4z)= | | 11-10x=50-31x | | 8*N+6-2N=34 | | 2x+7=-43-8x | | 2x+7=-43-8 | | 5x+5=3x-7 | | 3x+8=2y-x-6 | | 4z+7(3z-4)= | | (y-9)(y-2)= | | 3x-7=x+9 |